Aux origines du classicisme : calligraphes et bibliophiles au temps des dynasties mongoles (les Ilkhanides et les Djalajirides 656-814/1258-1411) - Ben Azzouna, Nourane (Islamic manuscripts and books, 2018)
Cet ouvrage explore une pe¿¿riode charnie¿¿re de l'histoire du livre islamique et iranien: la pe¿¿riode mongole envisage¿¿e dans le long terme, sous les dynasties ilkhanide et djalayiride. Il e¿¿tudie la question de la maturation de la calligraphie arabe classique a¿¿ travers la vie et l'¿¿uvre de Ya¿¿qu¿¿t al-Musta¿¿s¿Đimi¿¿ qui sont, pour la premie¿¿re fois, soumises a¿¿ une analyse syste¿¿matique, mettant en avant l'importance de son e¿¿cole et des mai¿¿tres bagdadiens pour les arts du livre des de¿¿cennies suivantes. L'ouvrage se penche aussi sur les manuscrits des Ilkhans musulmans et du vizir Rashi¿¿d al-Di¿¿n dans le cadre de la proble¿¿matique de la naissance de la kita¿¿bkha¿¿nah et de l'affirmation du statut des calligraphes et des peintres sous les derniers Ilkhanides et les Djalayirides. This book explores a pivotal period in the history of the book in the Islamic world and Iran, id est the Mongol period viewed in a long-term perspective, under the Ilkhanid and the Djalayirid dynasties. It examines the issue of the maturation of classical Arabic calligraphy through the life and work of Ya¿¿qu¿¿t al-Musta¿¿s¿Đimi¿¿, which are for the first time subjected to a systematic analysis, highlighting the importance of his school and the Baghdadi masters for the arts of the book of the following decades. The study also looks at the manuscripts of the Muslim Ilkhans and the Vizier Rashi¿¿d al-Di¿¿n in the context of the birth of the kita¿¿bkha¿¿nah and the rise in the status of calligraphers and painters under the last Ilkhanids and the Djalayirids.